Novel Machine Vision Image Guidance System Significantly Reduces Procedural Time and Radiation Exposure Compared With 2-dimensional Fluoroscopy-based Guidance in Pediatric Deformity Surgery. Issue 5 (6th May 2023) - Comstock, Christopher P.; Wait, Eric
Abstract : Background: Intraoperative 2-dimensional (2D) fluoroscopy imaging has been commonly adopted for guidance during complex pediatric spinal deformity correction. Despite the benefits, fluoroscopy imaging emits harmful ionizing radiation, which has been well-established to have deleterious effects on the surgeon and operating room staff. This study investigated the difference in intraoperative fluoroscopy time and radiation exposure during pediatric spine surgery between 2D fluoroscopy-based navigation and a novel machine vision navigation system [machine vision image guidance system (MvIGS)]. Methods: This retrospective chart review was conducted at a pediatric hospital with patients who underwent posterior spinal fusion for spinal deformity correction from 2018 to 2021. Patient allocation to the navigation modality was determined by the date of their surgery and the date of implementation of the MvIGS. Both modalities were the standard of care. Intraoperative radiation exposure was collected from the fluoroscopy system reports. Results: A total of 1442 pedicle screws were placed in 77 children: 714 using MvIGS and 728 using 2D fluoroscopy. There were no significant differences in the male-to-female ratio, age range, body mass index, distribution of spinal pathologies, number of levels operated on, types of levels operated on, and the number of pedicle screws implanted. Total intraoperative fluoroscopy time was significantly reduced in cases utilizing MvIGS (18.6 ± 6.3 s) compared with 2D fluoroscopy (58.5 ± 19.0 s) ( P < 0.001). This represents a relative reduction of 68%. Intraoperative radiation dose area product and cumulative air kerma were reduced by 66% (0.69 ± 0.62 vs 2.0 ± 2.1 Gycm 2, P < 0.001) and 66% (3.4 ± 3.2 vs 9.9 ± 10.5 mGy, P < 0.001) respectively. The length of stay displayed a decreasing trend with MVIGS, and the operative time was significantly reduced in MvIGS compared with 2D fluoroscopy for an average of 63.6 minutes (294.5 ± 15.5 vs 358.1 ± 60.6 min, P < 0.001). Conclusion: In pediatric spinal deformity correction surgery, MvIGS was able to significantly reduce intraoperative fluoroscopy time, intraoperative radiation exposure, and total surgical time, compared with traditional fluoroscopy methods. MvIGS reduced the operative time by 63.6 minutes and reduced intraoperative radiation exposure by 66%, which may play an important role in reducing the risks to the surgeon and operating room staff associated with radiation in spinal surgery procedures. Level of Evidence: Level III; retrospective comparative study.